Overview and Risk Identification of Garlic Seed Farming in Sembalun District, East Lombok Regency, Indonesia - Idiatul Fitri Danasari; Ni Luh Sri Supartiningsih; Sri Maryati; Ni Made Wirastika Sari; Baiq Rika Ayu Febrilia (Jurnal Penelitian Pendidikan IPA, 2023)
Sembalun district has known as one of places with high potential to generate garlic seed that can support national demand for garlic seed in Indonesia. In this regard, it is important to identify the risk of garlic seed farming in order to reduce the probability of risk that might be occur. This research aims to view and identify the risk of garlic seed farming in Sembalun District. Data were collected using questionnaires from 35 respondents, consist of 30 farmers and 5 garlic seed stockmen. The respondents were choose using accidental sampling in two villages namely Sembalun Bumbung Village and Sembalung Lawang Village. Data were analysed using descriptive method to describe the condition of garlic seed farming in Sembalun District. Moreover, fishbone diagram was used to identify of the risk of garlic seed farming. The results showed that there were five main sources of risk in garlic seed farming in Sembalun District such as 1) risk of production, 2) risk of price and market, 3) risk of financial, 4) risk of social and law, and 5) risk of human resources. Risk of production, price and market were the biggest risk that they were faced in producing garlic seed in Sembalun District.